Aktivisme Digital dalam Konteks Penggalangan Donasi Fandom BTS (ARMY) Indonesia Melalui Twitter - Nawan Sumardiono (Program Studi Ilmu Komunikasi, 2022)
Fandoms often carry out social activities to maintain their positive image, one of which is through digital media. This study explores how fandom uses digital media to carry out activism. This research was conducted using a qualitative approach. Meanwhile, the method used is a case study. To analyze the data, the researcher used the concept of digital activism. Based on the analysis, it is found that the use of certain momentum that is closely related to a group can support the success of digital activism. In addition, the message that is disseminated to carry out persuasion is important to be narrated by touching the emotional side of the individual. Transparency in the implementation of digital activism is also something that needs to be managed properly to support the success of digital activism being carried out.